2014
DOI: 10.1136/bjsports-2014-093494.305
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fifa 11+ as an Injury Prevention Program in Youth Futsal Players

Abstract: Background Futsal is a high risk sport, especially in youth level. But none has studied the application of FIFA 11+, the football injury prevention program among youth futsal players in Indonesia. Objective To determine the effectiveness of FIFA 11+ in improving physical fitness components affecting injury risks among youth futsal players. Design This experimental study was recruiting two groups of youth futsal players by doing purposive/judgmental random sampling to the senior high school futsal teams in Yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…Seven utilized Nordic hamstring exercises that have elsewhere been shown to increase eccentric hamstring strength, 30 and help prevent knee injuries (eg, ACLs). 19,33 Zein et al 47 and Pasanen et al 35 also confirmed that strength and jump time improved following use of a FIFA 111 or similar warm-up program. Strength imbalances, such as the hamstring:quadriceps ratio, are associated with a greater likelihood of hamstring injuries, 2 and Daneshjoo et al 4 showed that 8 weeks of a FIFA 111 IPP improved knee strength ratios.…”
Section: Discussionmentioning
confidence: 91%
“…Seven utilized Nordic hamstring exercises that have elsewhere been shown to increase eccentric hamstring strength, 30 and help prevent knee injuries (eg, ACLs). 19,33 Zein et al 47 and Pasanen et al 35 also confirmed that strength and jump time improved following use of a FIFA 111 or similar warm-up program. Strength imbalances, such as the hamstring:quadriceps ratio, are associated with a greater likelihood of hamstring injuries, 2 and Daneshjoo et al 4 showed that 8 weeks of a FIFA 111 IPP improved knee strength ratios.…”
Section: Discussionmentioning
confidence: 91%
“…Table 1 summarizes the basic characteristics of the 16 studies included in the review. 9,10,12,13,21,22–32 All of these studies are randomized controlled trials. The sample size ranges from 20 to 122, with a mean of 23 participants.…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies have focused on adolescent athletes between the ages of 10 and 16, and the other seven studies have focused on young adults aged from 17 and older. 9,10,21,23,24,30,32 Moreover, ten studies have included only male athletes, two studies included only female athletes, 25,26 three do not report on gender distribution, 13,21,32 and the remaining one study had a female percentage of 5%. 31 Fourteen studies recruited amateur players, and the remaining two studies recruited elite players.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies reporting the effects of this program on male athletes under 13 are still limited. In addition to the age factor, it is worth noting that despite the similarities between futsal and soccer, there is still a lack of research concerning the use of FIFA 11+ in young futsal athletes 14 .…”
Section: Introductionmentioning
confidence: 99%